Kepemimpinan Kiai dalam Manajemen Sekolah Berbasis Pesantren - Abdullah Muntaha; Andi Asyhari (At Tadbir: Journal of Islamic Education Management is published by the Islamic Education Management Study Programme, IAI al Urwatul Wutsqo, Jombang, East Java, Indonesia., 2025)
This study aims to reveal the role of kiai as a central figure in leadership and management of education in Islamic boarding schools, as well as its impact on the integration of Islamic values ??in the education system at SMAS Al-Hikmah 2 Sirampog Brebes. This study uses a qualitative approach with a case study method, where data is obtained through interviews, observations, and documentation to explore the dynamics of leadership and management of Islamic boarding schools. The results of the study indicate that kiai play a dominant role in strategic decision-making and the development of the school's vision and mission. Although the principal is responsible for administration, long-term policies still depend on the direction of the kiai. The kiai also succeeded in integrating Islamic values ??into school activities, such as congregational prayer and religious studies, which support the formation of student character. However, there is tension between the flexible tradition of Islamic boarding schools and more structured and modern managerial demands. This study provides theoretical contributions to the development of charismatic and spiritual leadership models in Islamic boarding schools, as well as practical contributions for education managers in developing a managerial system that accommodates spiritual values ??and Islamic boarding school traditions, but still prioritizes efficiency and professionalism.